Key Performance Indicators to Benchmark Hospital Information Systems – A Delphi Study - Hübner-Bloder, G.; Ammenwerth, E. (Methods of Information in Medicine, 2009)
Objectives: To identify the key performance indicators for hospital information systems (HIS) that can be used for HIS benchmarking.Methods: A Delphi survey with one qualitative and two quantitative rounds. Forty-four HIS experts from health care IT practice and academia participated in all three rounds.Results: Seventy-seven performance indicators were identified and organized into eight categories: technical quality, software quality, architecture and interface quality, IT vendor quality, IT support and IT department quality, workflow support quality, IT outcome quality, and IT costs. The highest ranked indicators are related to clinical workflow support and user satisfaction. Isolated technical indicators or cost indicators were not seen as useful. The experts favored an interdisciplinary group of all the stakeholders, led by hospital management, to conduct the HIS benchmarking. They proposed benchmarking activities both in regular (annual) intervals as well as at defined events (for example after IT introduction). Most of the experts stated that in their institutions no HIS benchmarking activities are being performed at the moment.Conclusion: In the context of IT governance, IT benchmarking is gaining importance in the healthcare area. The found indicators reflect the view of health care IT professionals and researchers. Research is needed to further validate and operationalize key performance indicators, to provide an IT benchmarking framework, and to provide open repositories for a comparison of the HIS benchmarks of different hospitals.
Keywords: Benchmarking; hospital information systems; medical informatics; Delphi technique; quality indicators; key performance indicators; user satisfaction